Taxifolin improves inflammatory injury of human bronchial epithelial cells by inhibiting matrix metalloproteinase (MMP) 10 via Wnt/β-catenin pathway. Issue 1 (1st January 2022) - Chen, Youhua; Mei, Yan; Yang, Lu; Li, Weibin; Zhou, Yu; He, Surong; Liang, Jie
ABSTRACT: Taxifolin (TXL), also known as dihydroquercetin, is one of the most important flavonoids prevalent across the plant kingdom. Increasing evidence has demonstrated its critical role in respiratory diseases. The present study aims to reveal the detailed mechanism in TNF-α-stimulated BEAS-2B cells by which TXL might exert effects on the development of asthma. Cell viability detection of BEAS-2B treated with TXL before and after TNF-α induction employed MMT. The expressions of inflammatory cytokines, MUC5AC and ICAM-1 were determined by quantitative reverse transcription PCR (RT-qPCR), enzyme-linked immunosorbent assay (ELISA) and Western blot after TXL was exposed to an in vitro asthma model. Then, light transmittance and apoptosis were then measured employing fluorescein transmittance, TUNEL and Western blot. After overexpressing MMP10, the abovementioned assays were performed again. Finally, the association between Wnt/β-catenin pathway and MMP10 was confirmed by detecting the proteins in this pathway. TXL increases the cell viability of TNF-induced BEAS-2B cells. TXL suppressed the inflammation, mucus formation, and apoptosis in TNF-α-induced BEAS-2B cells. Furthermore, after the prediction of binding sites between TXL and MMP10, it was found that overexpression of MMP10 reversed the effects of TXL on suppressing the progression of TNF-α-induced BEAS-2B cells. Finally, TXL blocked Wnt/β-catenin pathway by inhibiting MMP10 expression. TXL can be a promising drug for the treatment of asthma due to its inhibition of MMP10 expression by blocking Wnt/β-catenin pathway. Future experimental in vivo studies of asthma on this commonly used bioactive flavonoid could open new avenues for the therapies of asthma.